Survival analysis of transarterial radioembolization with yttrium-90 for hepatocellular carcinoma patients with HBV infection - She, Wong Hoi; Cheung, Tan To; Yau, Thomas C. C.; Chan, Albert C. Y.; Chok, Kenneth S. H.; Chu, Ferdinand S. K.; Liu, Rico K. Y.; Poon, Ronnie T. P.; Chan, See Ching; Fan, Sheung Tat; Lo, Chung Mau (HepatoBiliary Surgery and Nutrition, 2014)
Introduction: For patients with resectable hepatocellular carcinoma (HCC), hepatectomy remains one of the best treatment options to provide long-term survival. However, more than 50% of the patients have unresectable disease upon diagnosis even though there are no distant metastases. Transarterial chemoembolization (TACE) is a well-established treatment option that offers a palliative survival benefit for this group of patients. A better treatment for unresectable HCC has been sought after. There is some evidence that transarterial radioembolization (TARE) with the agent yttrium-90 produces encouraging outcomes, especially in patients with portal vein tumor thrombus. This study aims to analyze the outcomes of TARE at our center. Methods: From August 2009 to April 2013, 16 patients underwent TARE at our center. Sixteen patients with similar tumor characteristics were selected to undergo TACE alone for comparison. A retrospective analysis of the prospectively collected data of the patients was conducted. Only patients with newly diagnosed primary tumors were included in this study. Results: The median survival for patients having TARE was 19.9 versus 14.0 months in the TACE group (P=0.615). There was no difference in terms of tumor response according to the modified Response Evaluation Criteria in Solid Tumors (mRECIST) (P=0.632). The 1-, 2- and 3-year survival rates in the TARE group were 80.0%, 30.5% and 20.3% respectively. The 1-year survival in the TACE group was 58.3% (P=0.615). For patients who had major vascular invasion (eight in each group), the 1- and 2-year survival rates in the TARE group were 62.5% and 15.6% respectively, while the 1-year survival in the TACE group was 35.0% (P=0.664). Conclusions: The two groups showed similar results in terms of tumor response and overall survival benefit. TARE might provide a survival benefit for patients with major vessel invasion.